2020
DOI: 10.3390/ijerph17072176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Activity on Parental Rejection and Body Image Perceptions

Abstract: The present study investigated the potential moderating role of physical activity on the relationship between parental rejection and poor body image perceptions. Late adolescents and young adults from Turkey (N = 373; 256 females/117 males) reported their memories of upbringing (Egna Minnen Beträffande Uppfostran/EMBU) related to both their mother and father, respectively, levels of physical activity (International Physical Activity Questionnaires/IPAQ), and body image perception (Body Cathexis Scale/body diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…This result can be compared to that of a Canadian study carried out with people with obesity (Baillot et al, 2020), which found that participants with experienced lower levels of social physique anxiety had higher levels of moderate-to-vigorous physical activity. Moreover, physical exercise may positively influence the individual's self-assessment of body image (Naivar Sen et al, 2020). A scoping review (Sabiston et al, 2018) pointed out that based on results and the most frequent published associations, participation in physical activity and sport was related to a more positive body image, without causal conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be compared to that of a Canadian study carried out with people with obesity (Baillot et al, 2020), which found that participants with experienced lower levels of social physique anxiety had higher levels of moderate-to-vigorous physical activity. Moreover, physical exercise may positively influence the individual's self-assessment of body image (Naivar Sen et al, 2020). A scoping review (Sabiston et al, 2018) pointed out that based on results and the most frequent published associations, participation in physical activity and sport was related to a more positive body image, without causal conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps somewhat paradoxically, individuals with binge‐spectrum EDs also engage in adaptive exercise (i.e., exercise that is neither driven nor compensatory). This type of exercise (e.g., for enjoyment and/or health improvement) is associated with positive physical and psychological effects, social benefits, and reduced ED symptoms (Pendleton et al., 2002; Sen et al., 2020; Vocks et al., 2009). Previous research suggests that some individuals with binge‐spectrum EDs may engage in a mix of adaptive and maladaptive exercise episodes, while many others engage in purely adaptive exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps even more notably, participants frequently endorsed exercising for both maladaptive (i.e., to influence shape and weight, to avoid guilt) and adaptive (i.e., for health improvement or enjoyment) reasons during the same episode (Lampe, Forman, et al., 2021; Lampe, Trainor, et al., 2021). Furthermore, although the ED field typically focuses on maladaptive exercise behaviour (Scharmer et al., 2020), preliminary evidence suggests that increasing adaptive exercise has the potential to reduce ED pathology by reducing NA and body dissatisfaction and increasing positive affect (PA) and self‐efficacy (Lampe, Forman, et al., 2021; Pendleton et al., 2002; Sen et al., 2020; Vocks et al., 2009). Thus, to improve treatment outcomes for binge‐spectrum EDs, interventions must be able to distinguish and target maladaptive motivations for exercise without discouraging adaptive motivations for exercise.…”
Section: Introductionmentioning
confidence: 99%